Grb2-associated binder 1 polymorphism was associated with the risk of Helicobactor pylori infection and gastric atrophy - Goto, Yasuyuki; Ando, Takafumi; Nishio, Kazuko; Kawai, Sayo; Ishida, Yoshiko; Naito, Mariko; Goto, Hidemi; Hamajima, Nobuyuki (International journal of medical sciences, 2007)
Various single nucleotide polymorphisms (SNPs) have explained the association between Helicobacter pylori (H. pylori) and gastric atrophy and cancer. This study investigated the associations of Grb2 associated binder 1 (Gab1) polymorphism and the combination of PTPN11 gene encoding src homology 2 domain-containing protein tyrosine phosphatase-2 (SHP2) and Gab1 gene with gastric cancer and gastric atrophy among H. pylori seropositive subjects. A single nucleotide polymorphism at intron 2 of Gab1 (JST164345) was examined for 454 Japanese health checkup examinees (126 males and 328 females) aged 35 to 85 without a history of gastric cancer and 202 gastric cancer patients (134 males and 68 females) aged 33 to 94 with pathologically confirmed diagnosis of gastric adenocarcinoma. The decreased OR of the Gab1 A/A for H. pylori seropositivity was 0.25 (95% confidence interval (CI): 0.08-0.71). Among seropositive healthy controls, the OR of the Gab1 G/A+A/A for gastric atrophy was significant (OR=1.95, 95% CI: 1.12 -3.40). Seropositive individuals with PTPN11 G/G and Gab1 G/A+A/A demonstrated the highest risk of gastric atrophy with significance (OR=3.49, 95% CI: 1.54-7.90) relative to PTPN11 G/A+A/A and Gab1 G/G, the lowest risk combination, as a reference. However, the gene-gene interaction between PTPN11 and Gab1 was not observed (OR=1.39, 95% CI: 0.41-4.66). Compared to gastric cancer case, the Gab1 did not influence the step of atrophy/metaplasia-gastric cancer sequence. This study represents that the Gab1 polymorphism was associated with the low risk of H. pylori infection and the high risk of gastric atrophy among seropositive healthy controls, and that seropositive individuals with PTPN11 G/G and Gab1 G/A+G/G were associated with the greatest risk of gastric atrophy. These findings require confirmation in much larger studies.